Extranodal Natural Killer/T-Cell Lymphoma, Nasal Type: Basic Science and Clinical Progress - Harabuchi, Yasuaki; Takahara, Miki; Kishibe, Kan; Nagato, Toshihiro; Kumai, Takumi (Frontiers in Pediatrics, 2019)
Nasal natural killer (NK)/T-cell lymphoma (NNKTL) is characterized by progressive ulceration and necrosis of the nasal cavity and midline facial tissues. Histological findings of the lymphoma include angiocentric and polymorphous lymphoreticular infiltrates, which are called polymorphic reticulosis. Surface antigens, NK-cell marker CD56, as well as pan-T antigen CD2, cytoplasmic CD3 (CD3ε), and CD45 were expressed on the lymphoma cells. The origin of the lymphoma is thought to be either NK-cell lineage without T-cell receptor (TCR) rearrangement or T-cell lineage with γδ TCR rearrangement. Since the authors first demonstrated the presence of Epstein Barr virus (EBV)-DNA and EBV-oncogenic proteins, the lymphoma is now classified as one of the EBV-associated malignancies. The NNKTL cells produce IL-9, IL-10, interferon-γ-inducible protein-10 (IP-10), and chemokines possibly due to EBV-oncogenic proteins in the lymphoma cells and such factors take an important part in the cell proliferation and invasion in an autocrine manner. Clinically, serum EBV-DNA copy number is useful as a specific tumor marker and a predictive prognostic factor. The prognosis of this lymphoma is poor because of its rapid local progression and distant metastases. The authors designed arterial infusion chemotherapy from superficial temporal artery in combination with radiotherapy, and showed a favorable clinical outcome. This review addresses the epidemiologic, clinical, pathological, and virological characteristics of NNKTL.